Light-induced free radical alkylation of polynucleotides and their enzymatic digestion. - Leonov, D (1977)
Ultraviolet light-induced free radical alkylation with 2-propanol or D-ribose, initiated with di-tert-butyl peroxide, of poly (G), poly (U20G), and poly(A) led to the substitution of the appropriate group for the H-8 atom of the purines and addition across the 5,6-double bond of the pyrimidines. The alkylated polynucleotides were subjected to nucleolytic digestion with several nucleases. T1-RNase digestion of poly(G) irradiated with 2-propanol gave a mixture of the modified and non-modified mononucleotides. Similarly, pancreatic RNase digestion of the irradiated poly(U20G) resulted in a mixture of the appropriate mononucleotides. A T2-RNase treatment of poly(A) irradiated with 2-propanol gave the modified Ado-21:3'-P, while T2-RNase digestion of poly(A) irradiated with D-ribose led to the cyclic modified mononucleotides, in addition to the modified mononucleotides.